EFFECTIVE HUMAN RESOURCE MANAGEMENT STRATEGIES IN ISLAMIC BOARDING SCHOOLS - Syadiyah, Cholifatus; Rindaningsih, Ida (Antis-Publisher, 2024)
Objective: This study examines human resource (HR) management strategies within Islamic boarding schools (Pesantren) in Indonesia to address challenges posed by modernization and globalization while maintaining their role as vital centers of Islamic education. Method: Employing a literature review approach, the study analyzes the concept, planning, and application of HR management grounded in Islamic values. Results: The findings reveal that effective HR management in Pesantren includes comprehensive recruitment planning, continuous professional development for educators and administrative staff, systematic performance evaluation, and fostering a supportive organizational culture rooted in Islamic principles. These strategies collectively enhance the performance of all stakeholders, including students, while ensuring alignment with the institution’s educational and spiritual goals. Novelty: This research underscores the integration of Islamic values into HR management as a distinctive and adaptive framework, enabling Pesantren to not only sustain their educational relevance but also compete effectively in the modern era, thereby addressing the needs of future generations.